An evaluation of the Homunculi Approach as an intervention for pupils with autism spectrum experiencing anxiety - Maydew, Harriet (2018)
Young people with Autism Spectrum (AS) are a population at risk of experiencing Mental Health Problems (MHPs); with anxiety being the most commonly reported internalising MHP for this population (Skokauskas & Gallagher, 2012). Schools have been identified as well placed to support pupils experiencing MHPs (DoH & DfE, 2017). The primary aim of the present research was to evaluate the Homunculi Approach (Greig & MacKay, 2013b) as an intervention for secondary aged pupils with AS experiencing anxiety. The secondary aim of the research was to explore factors affecting implementation of the Homunculi Approach. An embedded mixed methods design was utilised where the primary research aim (Phase 1) was supplemented by the secondary research aim (Phase 2). Phase 1 consisted of an A-B single case experimental design (SCED) with four participants across four different secondary schools. Anxiety was measured through: repeated behavioural observations and a weekly anxiety questionnaire (PI-ED); pre and post intervention measures, completed by the young people, parents and teachers (SCAS, SAS-TF and SDQ); and measures which occur organically within the Homunculi Approach intervention. Phase 2 of the research explored the factors which affected implementation of the intervention in schools by interviewing the school staff who delivered the Homunculi Approach. The data was collected using an activity theory framework. The findings from the research indicated the intervention was effective in reducing anxiety for two participants, and ineffective in reducing anxiety for the other two participants. Several implementation factors were identified which may have impacted on the effectiveness of the Homunculi Approach when delivered by members of school staff in secondary schools. The findings are discussed in relation to the literature. Limitations of the research, such as the small sample size and possible impact of external factors, are acknowledged. Possible implications and ideas for future research are presented.